2022
DOI: 10.1097/md.0000000000029338
|View full text |Cite
|
Sign up to set email alerts
|

A case report of IgG4-related respiratory disease with pleural effusion and a literature review

Abstract: Rationale: IgG4-related respiratory disease (IgG4-RRD) is a chronic autoimmune disease that affects the respiratory system and organs outside the respiratory system. This study explored the diagnosis and treatment of a case of IgG4-RRD with unilateral pleural effusion diagnosed using medical thoracoscopy, and provides an associated literature review. This report summarizes the clinical characteristics of IgG4-RRD involving the pleura to improve the diagnosis of this disease.Patient concerns: A 39-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In IgG4-PL patients, it is typically observed that CRP levels are within normal range. However, in the cases we analyzed, 10 individuals demonstrated a mild increase in CRP levels (8,13,18,20,21,27,28,33,36,37). It is important to highlight the contrast between IgG4-PL and conditions such as ANCA associated vasculitis and multicentric Castleman disease (MCD) when considering the levels of inflammatory markers like CRP.…”
Section: Kasashima Et Al (mentioning
confidence: 96%
“…In IgG4-PL patients, it is typically observed that CRP levels are within normal range. However, in the cases we analyzed, 10 individuals demonstrated a mild increase in CRP levels (8,13,18,20,21,27,28,33,36,37). It is important to highlight the contrast between IgG4-PL and conditions such as ANCA associated vasculitis and multicentric Castleman disease (MCD) when considering the levels of inflammatory markers like CRP.…”
Section: Kasashima Et Al (mentioning
confidence: 96%